Free will and deontology of health operators: Libre albedrío y la deontología de los operadores de salud - Carcausto, Wilfredo (2019)
In public hospitals there is a massive demand for health services and workers of various specialties play a vital role in supplying such demand. Objective: to reflect on medical action and free will. Method: narrative-reflexive bibliographic review. Conclusions: human action and decision is always conditioned, although it has a margin to act as it should and not as it should. In health services, this margin implies that the doctor abandons his protocol commitment and acts according to his free will without delimiting possible responsibilities in the consequences that these could have on patients. The acting of the doctor regulated by the protocols of medicine and deontology emerges in the patient an absolute confidence, therefore, there is no reason for intervention of the ethical and deontological surveillance committee, although, if it were the opposite, it should do so. Keywords: Ethical Theory, Humanism, Freedom (Source: MeSH, NLM).